A new form of the mole vole Ellobius tancrei Blasius, 1884 (Mammalia, Rodentia) with the lowest chromosome number - Bakloushinskaya, Irina (Pensoft Publishers, 2013)
Abstract. The subterranean mole vole, Ellobius tancrei, with aspecific variability in autosomes (2n = 31–54) and unusual sex chromosomes (XX in males and females), represents an amazing model for studying the role of chromosome changes in speciation. New materials from the upper reaches of the Surkhob River in the Pamiro-Alay mountains resulted in the discovery of a new form with 2n = 30. The application of Zoo-FISH and G-banding methods allowed the detection of 13 pairs of autosomes as Robertsonian metacentrics originated after fusions of acrocentrics of an assumed ancestral karyotype of Ellobius tancrei with 2n = 54. The sex chromosomes (XX, in both sexes) and one pair of acrocentric autosomes are the only acrocentrics in this karyotype, and the set with 2n = 30 possesses the lowest possible chromosome number among populations of Ellobius tancrei.